Sweden now 1989-II - IMU-Testologen AB (IMU-Testologen AB, 1994)
In the mid-1960s, Testologen AB in collaboration with a group of advertisers, introduced a new way of investigation, where data about the target groups - socio-economic data, interests, purchasing habits, possessions, buying intentions - and data on reading habits were collected in the same survey. At SND there are now surveys available from the Sweden Now series covering a 20-year period, 1972-1991.
In the 1989 survey there are questions about existing household equipment and purchases planned for the next couple of years. The respondent also had to state on a scale ranging from ´very interested´ to ´very uninterested´ how interested she/he was in 67 various subjects and activities covering: Consumer durables; Consumer non-durables; Personal care, health and fashion; Plants and pets; Pleasure and leisure time; Residency and home hobbies; Social and political activities. Another question deals with how much money annually the respondent spends on gambling, clothes, entertainment etc. The respondent also had to state how often various shops were visited, how often various types of advertisements were noticed, and how often various products were bought. For some hundred various dailies, weeklies and monthly magazines the respondent had to state how often they were read. The respondents were also asked how often they used different means of transport. Background information covers gender, age, marital status, occupation, education, housing, place of living and household composition.

Purpose:

Collect broad information about interests, purchasing habits and media choices

I mitten av 1960-talet introducerade Testologen AB, i samverkan med en grupp annonsörer, en ny undersökningsform som innebar att målgruppsdata - socio-ekonomiska data, intressen, köpvanor, innehav, köpavsikter mm - och läsvanedata insamlades i en och samma undersökning. Undersökningarna går under benämningen 'Sverige Nu', men databanken marknadsförs under benämningen ORVESTO. Namnet ORVESTO markerar målsättningen att täcka många mediagrupper: OR som i organisationspress, VE som i veckopress och STO som i storstadspress. Vid SND finns ORVESTO-undersökningar som täcker en tjuguårsperiod, 1979-1991 tillgängliga.
I 1989 års undersökning ställs frågor om vilken utrustning som finns i hushållet och om vilka inköp man planerar göra inom de närmaste två åren. Respondenten får även på en skala 'mycket intresserad-mycket ointresserad' ange sitt intresse för 67 olika ämnen och aktiviteter omfattande: Konsumentkapitalvaror; Dagligvaror; Hygien, hälsa och mode; Växter och husdjur; Nöjen och fritid; Boende och hemmahobbies; samt Samhällsfrågor mm. En annan fråga gäller hur mycket pengar respondenten under ett år normalt lägger ner på bland annat spel, kläder och nöjen. Respondenten fick också ange hur ofta olika typer av affärer besöks, hur ofta man ser olika typer av reklam och hur ofta man köper vissa produkter. För ett stort antal dags-, vecko-, 14-dagars- och månadstidningar anges hur ofta man läser den. Bakgrundsvariablerna innehåller uppgifter om kön, ålder, civilstånd, förvärvsarbete, utbildning, bostad och bostadsort samt hushållets sammansättning.

Syfte:

Samla in en bred information om intressen, köpvanor och mediaval
ORVESTO 1989-II
Sverige nu 1989-II
Keywords: Consumption and consumer behaviour; Konsumtion och konsumentbeteende; Media; Media; Public relations; Public relations; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap